Self-powered multifunctional sensing based on super-elastic fibers by soluble-core thermal drawing - Chen, Mengxiao; Wang, Zhe; Zhang, Qichong; Wang, Zhixun; Liu, Wei; Chen, Ming; Wei, Lei (Nature communications, 2021)
The well-developed preform-to-fiber thermal drawing technique owns the benefit to maintain the cross-section architecture and obtain an individual micro-scale strand of fiber with the extended length up to thousand meters. In this work, we propose and demonstrate a two-step soluble-core fabrication method by combining such an inherently scalable manufacturing method with simple post-draw processing to explore the low viscosity polymer fibers and the potential of soft fiber electronics. As a result, an ultra-stretchable conductive fiber is achieved, which maintains excellent conductivity even under 1900% strain or 1.5 kg load/impact freefalling from 0.8-m height. Moreover, by combining with triboelectric nanogenerator technique, this fiber acts as a self-powered self-adapting multi-dimensional sensor attached on sports gears to monitor sports performance while bearing sudden impacts. Next, owing to its remarkable waterproof and easy packaging properties, this fiber detector can sense different ion movements in various solutions, revealing the promising applications for large-area undersea detection. Though thermal drawing methods are attractive for fabricating fiber-based sensor devices, existing methods allow limited access to low viscosity and low modulus materials. Here, the authors demonstrate a two-step soluble-core fiber fabrication method with wide applicability to soft polymer materials.